Answer: ![y=-4](https://tex.z-dn.net/?f=y%3D-4)
<u>Subtract 4 from both sides</u>
<u></u>
<u></u>
<u></u>
<u>Divide both sides by 3</u>
<u></u>
<u></u>
<u></u>
<u></u>
<u></u>
Answer:
this should help
Step-by-step explanation:
https://answer-helper.com/mathematics/question16732528
okay i have question is this more than oonequestion Step-by-step explanation:
also confusing hope you pass cause would have failed
Answer:
3
Step-by-step explanation: now weres the 10000 points you scammer
Answer:
![\text{\boxed{\sf{D. \ No\ solution}}}](https://tex.z-dn.net/?f=%5Ctext%7B%5Cboxed%7B%5Csf%7BD.%20%5C%20No%5C%20%20solution%7D%7D%7D)
Step-by-step explanation:
Isolate the term of x and y from one side of the equation.
<h3>y=-4x-9 and y=-4x-1</h3>
First, you have to substitute of y=-4x-1.
![\Longrightarrow: \sf{[-4x-1=-4x-9]}](https://tex.z-dn.net/?f=%5CLongrightarrow%3A%20%5Csf%7B%5B-4x-1%3D-4x-9%5D%7D)
<u>Add by 4x from both sides.</u>
![\Longrightarrow: \sf{-4x-1+4x=-4x-9+4x}](https://tex.z-dn.net/?f=%5CLongrightarrow%3A%20%5Csf%7B-4x-1%2B4x%3D-4x-9%2B4x%7D)
<u>Solve.</u>
![\Rightarrow:\sf{-1=-9}\\\\\Rightarrow: \sf{(-9)-(-1)=-9+1=-8}\\\\\Rightarrow: \sf{8=0}](https://tex.z-dn.net/?f=%5CRightarrow%3A%5Csf%7B-1%3D-9%7D%5C%5C%5C%5C%5CRightarrow%3A%20%5Csf%7B%28-9%29-%28-1%29%3D-9%2B1%3D-8%7D%5C%5C%5C%5C%5CRightarrow%3A%20%5Csf%7B8%3D0%7D)
- <u>Therefore, the correct answer is "D. No solution".</u>
I hope this helps. Let me know if you have any questions.